Compactação de subleito de vias de loteamento residencial urbano : verificação de influência da cota do terreno e do índice pluviométrico - SILVA FILHO, Daury Sousa da (2024)
Belém receives a high volume of rainfall annually, its climatic and topographic conditions cause circumstances that provide high rainfall. Given the striking climatic aspect of the capital of Pará, certain civil construction works have a specific weakness exposed annually during the rainy seasonal period, these are paving works. This work aims to evaluate the influence of rainfall frequency, rainfall volume and terrain topography on the density and optimal humidity of the hot machined asphalt concrete pavement subgrade in the Bougainville project, located on the banks of Av. Augusto Montenegro, metropolitan region of Belém. The methodology of this work consists of statistical analysis of specific mass and optimum soil moisture data, collected in situ through technological control using control sheets by a specialized company using the sand bottle method and the Speedy, as recommended by DNER-ME 092/94 and DNER-ME 052/94, respectively, in relation to the variables: topographic elevation, number of rainy days preceding the compaction date by up to seven days and rainfall volume on these days. The data on the influencing variables, number of days with rain before compaction and accumulated millimetric volume of such days were obtained using as a reference the compaction dates contained in control sheets for consultation of the INMET meteorological station database through the address institution's website. Meanwhile, data on the topographic elevation variable was collected using as a reference the location coordinates contained in control sheets and sectorized map of the project for consultation in the Topographic website database. The collected data were treated through descriptive statistical analysis, where: means, modes, medians, standard deviations, coefficients of variation were obtained and, consequently, the correlation between pairs was verified, through Pearson's linear correlation: specific mass x quota, specific mass x rain in previous days, humidity x quota and humidity x rain in previous days. The evidence found in this work indicates that: the specific mass does not present a linear correlation in relation to the level and the rain in the days prior to compaction, while the humidity x level pair presents a weak positive linear correlation and the humidity x rain pair in the previous days presents a weak negative linear correlation. This study should be extended to other regional soils in order to validate the correlations obtained and expand its field of application.